The economic impact of economic transformation plan (ETP) on Malaysian economy by year 2020: An input-output analysis - Puasa, Ahmad Fauzi; Abdul Rashid, Zakariah; Raja Mohammad, Raja Zarina (2011)
Since independence, Malaysia has gradually built a robust and resilient economy with commendable growth. The country has almost eradicated hardcore poverty, and at the same time, been able to provide its society near universal access to basic health, education, communications and other public services. As a result, the quality of life for the vast majority of Malaysians has improved considerably. However, the end the journey as stipulated in Vision 2020 is to give good quality of life to the people in terms of sustainable and inclusive high‐income provides greater challenges given the current structural constraints. Considering the fact that the economy can bear a burden limited o its capacity, structural reform is needed, therein the ETP laying out expenditure plan for the NEM period. The resent paper found a marked structural gap between Malaysia and other selected more developed countries in terms of input‐output structure.